Applications of a novel biodetection system to saliva using protein fingerprints with data processing. Issue 12 (23rd July 2018) - Tominaga, Yuki; Usui, Kenji; Hirata, Akiyoshi; Ito, Hiro-O; Nokihara, Kiyoshi
Graphical abstract: Abstract: A fundamental method has been developed focusing on a facile and rapid examination of periodontal disease. Periodontal disease is an oral disease thought to affect 80% of adults, and early detection with treatment is desirable for the improvement of the quality of life. Unfortunately conventional methods are not consistent as the disease is caused by a number of undefined bacteria and detection relies on the skills of the dentist. Thus an objective detection system is required. We have performed an experiment on saliva using a novel biodetection system, designated PepTenChip®. A disease model for saliva was prepared using a specimen from a healthy subject and a mixture of hemoglobin (f-Hb) and lactate dehydrogenase (LDH), which is used as a periodontal disease marker protein with healthy saliva. PepTenChip® is a peptide microarray in which fluorescent labelled structured peptides are immobilized on a novel amorphous carbon substrate. Since the peptides used as capture molecules are fluorescently labelled, labeling of analytes is not necessary. The fluorescence intensity change before and after application of analytes are detected rather than the ON/OFF detection common to conventional microarrays using a set of antigen–antibody. The fluorescence intensity value changes according to the concentration of captured protein allowing the generation of protein fingerprint (PFP) and dendrograms. The present method does not rely on a "one to one" interaction, unlike conventional biodetection, and advantages can be envisaged in the case of an undefined or unknown cause of disease. The statistical analyses, such as multivariate analyses, allow classification of the type of proteins added in saliva as mimetics of disease. PepTenChip® system is useful and convenient for examination of periodontal disease in health care.